2011
DOI: 10.1007/s11064-010-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Resveratrol on the BDNF Gene Expression in the Hippocampus of the Rat Brain

Abstract: Resveratrol is a plant polyphenolic compound. Evidence indicates that resveratrol has beneficial effects against aging and neurodegenerative diseases. The goal of our study was in vivo examination of the effects of resveratrol on the abundance of mRNA encoding Brain Derived Neurotrophic Factor (BDNF) in the hippocampus of rat brain. Rats were administrated orally by different doses (2.5-20 mg/kg bwt) of resveratrol for 3, 10 and 30 days. Saline was used as control and 10% ethanol in saline was used as vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
(32 reference statements)
5
28
1
Order By: Relevance
“…The present study revealed that resveratrol concentration- and time-dependently increased BDNF and GDNF release in primary neuron-glia cultures. Similar results shown that resveratrol significantly induced BDNF gene expression in the hippocampus of rat brain and increased BDNF and GDNF production in primary astroglia-enriched cultures [31, 32]. In addition, It is interesting to note that although the application of either anti-BDNF or anti-GDNF antibodies inhibited resveratrol-mediated neurotrophic effects in primary neuron-glia cultures, the partial neurotrophic effects were still presented compared with the control cultures.…”
Section: Discussionsupporting
confidence: 65%
“…The present study revealed that resveratrol concentration- and time-dependently increased BDNF and GDNF release in primary neuron-glia cultures. Similar results shown that resveratrol significantly induced BDNF gene expression in the hippocampus of rat brain and increased BDNF and GDNF production in primary astroglia-enriched cultures [31, 32]. In addition, It is interesting to note that although the application of either anti-BDNF or anti-GDNF antibodies inhibited resveratrol-mediated neurotrophic effects in primary neuron-glia cultures, the partial neurotrophic effects were still presented compared with the control cultures.…”
Section: Discussionsupporting
confidence: 65%
“…16 In addition, although most research on resveratrol has demonstrated its ability to prevent cellular degeneration via decreased apoptosis, increased antioxidant activities, and anti-inflammatory effects, 17 resveratrol may also be able to reverse neural degeneration by increasing levels of BDNF. 18 The findings of these studies provide several potential mechanisms by which dietary supplementation with Concord grape juice could reverse the latent learning impairment normally observed in middle-aged male rats.…”
Section: Introductionmentioning
confidence: 93%
“…5 The anthocyanidins, proanthocyanidins, and resveratrol present in Concord grape juice may have caused the reversal of the latent learning deficit through their antioxidant properties. [13][14][15]17 In addition, these compounds could have acted to promote neurogenesis and increase synaptic plasticity in existing neurons by increasing brain levels of BDNF 14,18 and by increasing the number of dendrites and synapses. 16 These mechanisms could explain the current findings, as well as why dietary supplementation with Concord grape juice has been shown to reverse cognitive impairments in the Morris water maze task in aged rats, 2 and improve learning of verbal material, recognition memory, and spatial memory in humans.…”
Section: Concord Grape Juice Reverses the Latent Learning Impairmentmentioning
confidence: 99%
“…However, prenatal RSV treatment alleviated early and late gestational stress-induced cognitive deficits/dysfunction in rats on postnatal day 40, without affecting reduced cerebral Na + , K + -ATPase activity which is related to memory consolidation [316]. of spinal cord injured rats [322], iv) elevated BDNF in the hippocampal tissues of rats [323], v) reduced infarct volumes during the acute phase of ischemic stroke reducing brain injury in mice, with suppressed expression of IL-1β and TNF-α, microglial activation, and ROS production in the ischemic cortex (neuroprotective) [324].…”
Section: Effect Of Rsv On Other Neuronal Damagementioning
confidence: 99%